Factors affecting the effectiveness of closed circuit television surveillance in the United Arab Emirates - Al-Ashkari, Abdulla Salem (2024)
The United Arab Emirates governmental institutions are now developing innovative methods to employ smart devices like surveillance cameras to deliver improved services to its inhabitants that are conveniently accessible, precise, prompt, high-quality, and information-rich. Closed-Circuit Television cameras are widely employed in Abu Dhabi to maintain surveillance in order to support law enforcement and aid in crime control at UAE public institutions. The usage of CCTV cameras faces three key difficulties: a lack of awareness of how CCTV works, a lack of understanding of IT security, and an incorrect understanding of the responsibilities that various stakeholders play in preserving public safety. These reasons have stoked contentious discussions regarding the viability of CCTV surveillance rising public discomfort. The effectiveness of the CCTV surveillance system framework in the city and the role of technology in preserving public safety in the United Arab Emirates are the key topics of this thesis. This study investigates the effectiveness of Closed-Circuit Television (CCTV) surveillance systems in crime prevention in the United Arab Emirates. Utilizing a mixed-methods approach, the research combines quantitative and qualitative analyses to offer a comprehensive understanding of the impact of CCTV systems on public safety and crime deterrence. The quantitative component, comprising a survey distributed to 428 participants from various UAE governmental organizations, examines factors influencing CCTV effectiveness. These include location, institutional framework, social value, policy, centralized monitoring systems, technical capacity, authority control, and privacy. Structural Equation Modeling (SEM) is employed to analyze the relationships between these factors and the effectiveness of CCTV installation. Complementing this, the qualitative aspect involves semi-structured interviews and observations, targeting key personnel involved in CCTV operations. This approach provides deeper insights into the practical application and challenges of CCTV surveillance. The thematic analysis of qualitative data elucidates the nuances of public perception and operational effectiveness of CCTV systems. The findings reveal that several factors significantly impact the effectiveness of CCTV surveillance in crime prevention. Notably, technical capacity, policy, and location emerge as critical determinants. The study also uncovers the importance of a supportive institutional framework and public engagement in enhancing CCTV effectiveness. The research contributes to the field by proposing a comprehensive framework for CCTV surveillance in crime prevention, tailored to the UAE context. It highlights the necessity for a balanced approach that incorporates technological, policy, and human factors. The study's limitations and future research directions are also discussed, providing a pathway for further exploration in this evolving field.